Semotic Analysis of Patriarchal Relations in The Film "Barbie" - Esa, Qiran Ridha; Yuliana, Nina (Jurnal Sosial Sains dan Komunikasi, 2024)
Many men in Indonesia still think that men are above women. Even after watching the film Barbie, which is anti-patriarchal and has a strong message of gender equality, many men do not agree with the message conveyed by the film. The use of mass media in conveying communication messages is the right thing. The use of mass media such as Netflix, Disney Plus, and HBO makes it easier for readers to receive the messages contained in a film. Many films now raise social issues such as feminism, bullying, cybercrime, economic crisis, patriarchy and many more. This research aims to analyze the existence of patriarchal ideology displayed in scenes in the film Barbie. The theory used by researchers is John Fiske's Semiotics theory, the method used for research is qualitative research methods. Semiotic analysis is used to determine the signs of the patriarchal system displayed in the Barbie film by analyzing the scenes in the film. The method used in this research is descriptive analysis using a qualitative approach. The results of this research reveal that the scenes in the Barbie film contain deep messages such as patriarchy and the feminist movement. The scenes in this film also contain the message that women can be whatever they want without pressure or gender inequality occurring. This film tries to convey the role of women who can be anything with freedom without being haunted by other variables.There are three levels of coding in the Barbie film, such as Reality, Representation and Ideology Levels. The aspects that dominate the Barbie film are aspects of behavior, expression, conflict and patriarchy.